Identifikasi Program CSR pada Bidang Pendidikan di PT Suryabumi Agrolanggeng Kabupaten Penukal Abab Lematang Ilir (Pali) - Anggun; Desy Misnawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Corporate Social Responsibility (CSR) has now become a common behavior in Indonesia, but not all companies have implemented it. making education in Indonesia a quite complex problem. The role of the government, community and other parties including the business world is needed in developing education, as long as it is an effort to support government programs. The freeing up of the company's role gave rise to various forms of activities in the education sector. The type of research used is qualitative descriptive research with data sources from observation, interviews and documentation. When viewed from the data sources, the data collection uses primary data sources and secondary data sources. Identification of CSR Programs in the Education Sector at PT. Suryabumi Agrolanggeng has been implemented well, every year the company provides assistance for teachers' welfare, the construction of a prayer room for SMP Negeri 6, assistance for the construction of the building of SMK Negri 2 and many others in building quality education, making the nation's life intelligent and the welfare of teachers for the education sector in PALI Regency